2020
DOI: 10.1007/s00401-020-02158-2
|View full text |Cite
|
Sign up to set email alerts
|

Distribution patterns of tau pathology in progressive supranuclear palsy

Abstract: Progressive supranuclear palsy (PSP) is a 4R-tauopathy predominated by subcortical pathology in neurons, astrocytes, and oligodendroglia associated with various clinical phenotypes. In the present international study, we addressed the question of whether or not sequential distribution patterns can be recognized for PSP pathology. We evaluated heat maps and distribution patterns of neuronal, astroglial, and oligodendroglial tau pathologies and their combinations in different clinical subtypes of PSP in postmort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
394
8
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 288 publications
(455 citation statements)
references
References 50 publications
49
394
8
4
Order By: Relevance
“…In PSP, from postmortem studies, these include basal ganglia, thalamus, substantia nigra, premotor cortex, as well as the dentate nucleus and cerebellar white matter. In CBD, areas associated with the disease include cortex, thalamus, basal ganglia, and brainstem, without cerebellar involvement 48‐50 . However, in our study, the loss of synapses in PSP is global across the cortex, and not confined to the premotor and motor areas, and extends beyond the substantia nigra in the brainstem with pontine and medullary involvement.…”
Section: Discussionmentioning
confidence: 50%
“…In PSP, from postmortem studies, these include basal ganglia, thalamus, substantia nigra, premotor cortex, as well as the dentate nucleus and cerebellar white matter. In CBD, areas associated with the disease include cortex, thalamus, basal ganglia, and brainstem, without cerebellar involvement 48‐50 . However, in our study, the loss of synapses in PSP is global across the cortex, and not confined to the premotor and motor areas, and extends beyond the substantia nigra in the brainstem with pontine and medullary involvement.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, these results are in line with some neuropathological studies that described similar networks implied and differences in the global distribution and severity of tau pathology between PSP variants. 3,4,53,54 In fact, a recent neuropathological study observed common early vulnerability patterns that characterize all PSP clinical subtypes jointly (pallido-nigro-luysian axis), but different dynamics of propagation. 54 In other words, our findings suggest that despite the existence of probable neuropathological and functional differences between PSP variants, they may also share a common pattern that can serve as a PSP biomarker to discriminate PSP variants from PD patients and HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the accumulation of abnormal tau being the basis of all tauopathies, these diseases differ from each other with regard to the brain areas affected, the kind of tau aggregates, and the cell types in which the aggregates are found, which is either neurons or astrocyte or oligodendrocytes. For example in PSP, different from AD, pathological tau accumulations start in the neurons of subcortical and brainstem nuclei, in the oligodendrocytes of the globus pallidus, and in the astrocytes of the striatum, followed by tau accumulation in cortical astrocytes, neurons, and oligodendrocyte, respectively, with a fronto-parietal to temporal to occipital sequence [ 177 ].…”
Section: The Role Of Tau In Neurodegenerative Diseasesmentioning
confidence: 99%